Alterations of the SWI/SNF chromatin remodelling subunit‐BRG1 and BRM in hepatocellular carcinoma. (22nd October 2012) - Endo, Mio; Yasui, Kohichiroh; Zen, Yoh; Gen, Yasuyuki; Zen, Keika; Tsuji, Kazuhiro; Dohi, Osamu; Mitsuyoshi, Hironori; Tanaka, Shinji; Taniwaki, Masafumi; Nakanuma, Yasuni; Arii, Shigeki; et al.
Abstract Background The SWI/SNF chromatin remodelling complex, which contains either brahma‐related gene‐1 (BRG1) or brahma (BRM) as the catalytic ATPase, functions as a master regulator of gene expression. Aims To examine alterations of BRG1 and BRM in hepatocellular carcinoma (HCC). Methods We investigated DNA copy number aberrations in human HCC cell lines using a high‐density oligonucleotide microarray. We determined DNA copy numbers and expression levels of BRG1 and BRM genes in primary HCC tumours, and conducted further searches for mutations in BRG1 and BRM genes. Results Homozygous deletion of the BRG1 gene was found in HCC cell line SNU398. Copy number losses of BRG1 and BRM genes were observed in 14 (26%) and 7 (13%) of 54 primary HCC tumours respectively. We found four somatic missense mutations in the BRG1 gene in two of 36 primary HCC tumours, but no mutations in BRM gene. Expression of BRM mRNA, but not BRG1 mRNA, was significantly reduced in primary HCC tumours, compared to non‐tumour tissue counterparts. Immunohistochemical analyses of non‐tumour liver tissues showed that BRM protein was expressed in hepatocytes and bile‐duct epithelial cells, whereas BRG1 protein was expressed in bile‐duct epithelial cells, but not in hepatocytes. BRM protein expression was lost in nine (22.5%) of 40 HCC tumours. Loss of BRM protein expression was significantly associated with poor overall survival. Conclusion Reduced expression of BRM may contribute to the carcinogenesis of HCC. Although deletions and mutations in BRG1 gene were identified, the role of BRG1 in HCC tumourigenesis remains unclear.